ASME 2013 Gas Turbine India Conference 2013
DOI: 10.1115/gtindia2013-3683
|View full text |Cite
|
Sign up to set email alerts
|

NO Prediction in Turbulent Diffusion Flame Using Multiple Unsteady Laminar Flamelet Modeling

Abstract: The steady laminar flamelet model (SLFM) [1, 2] has been shown to be reasonably good for the predictions of mean temperature and the major species in turbulent flames [3, 4]. However, the SLFM approach has limitations in the prediction of the slow chemistry phenomena like NO formation [5, 6]. In case of SLFM, the turbulence and chemistry are coupled through a single variable, called scalar dissipation, which is representative of the strain inside the flow. The SLFM model is not able to respond to the steep cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…They studied the effect of different methods of initialization of the probability of finding particles and initialization region extended to fuel rich regions provided better results. [4] conducted a study on Sandia flame D and Delft flame III using multiple unsteady flamelet method and observed similar trends in NO predictions as in [12]. They also found that increasing the number of flamelets increased the accuracy of prediction in the Delft flame III whereas the results hardly improved for Sandia flame D. The present study extends the analysis on Sandia flames E and F that have not been studied before on these aspects while comparing with the finite rate chemistry-based approaches.…”
Section: Introductionsupporting
confidence: 75%
See 4 more Smart Citations
“…They studied the effect of different methods of initialization of the probability of finding particles and initialization region extended to fuel rich regions provided better results. [4] conducted a study on Sandia flame D and Delft flame III using multiple unsteady flamelet method and observed similar trends in NO predictions as in [12]. They also found that increasing the number of flamelets increased the accuracy of prediction in the Delft flame III whereas the results hardly improved for Sandia flame D. The present study extends the analysis on Sandia flames E and F that have not been studied before on these aspects while comparing with the finite rate chemistry-based approaches.…”
Section: Introductionsupporting
confidence: 75%
“…The steady laminar flamelet model (LFM) is used to model the turbulent-chemistry interaction to obtain a converged steady flow solution and then the Eulerian unsteady laminar flamelet model is used to model the slow kinetic species as a post processing on the steady-state, steady flamelet solution. The detailed description of the approach can be found in [13,4].…”
Section: Numerical Detailsmentioning
confidence: 99%
See 3 more Smart Citations